Opening of the “Altan sav”: about burial directions of the deceased person - Damdinsuren, Davaasuren (Tibetan Studies, 2025)
This article provides a comprehensive explanation of the method for determining the burial direction of a deceased person. We primarily referenced the following scriptures: - The 29th chapter, titled "The Horoscope of the Deceased" on pages 343-418 of the famous book “The good teachings of the Pug traditional astrology, the adornment of the wise, the pendant of Bindergarav, the treasure of the heart of the perfect astrologer” printed by the Tibetan wooden matrix (paper size 10.3x48.2, pages …) by Tibetan scholar Sanjaijamts. - The Second Book “Rules compiled into a single table for Right recognition of “Altan sav” (Golden Box) and the Five kinds of Dead Body and horoscope of the deceased, which helps both the living and the deceased” (Tibetan manuscript, paper size 8.7x26, 17 pages) by the Mongolian scholar Sumbe Khambа. - The Book “Brief Summary of the Horoscope for the Deceased, an Easy-to-Get Helper for All” (Tibetan manuscript, paper size 9.8x42, 26 pages) by the Mongolian scholar Luvsandagdan. In addition to these, we have selected and made easy to use the most important research materials on the theory of the Horoscope of the deceased person: - beet’ur dkar po’i gshin brtsis mdor bsdus mdo gzhung bzhugs (Author unknown, Tibetan manuscript, paper size 8.6x32, 16 pages). - Bindergarav's summary of the Horoscope of the deceased, the main scripture - The “Altan sav Sutra” (Mongolian manuscript, paper size 8.5x30.6, 21 pages). - The scripture "Protecting the Living from misfortunes and the Horoscope of the Deceased" (Tibetan manuscript, paper size 18x7.5, 24 pages). - A summary of the contents of the horoscope of the deceased, a dictionary of proceedings of the work gshin rtsi’i rnam bzhag mdor bsdus bya tshul gsal byed me long zhes by aba bzhugs so (Tibetan manuscript, 9 pages). - A summary of the contents of the horoscope of the deceased, a glossary of tasks to be done, and a guide to the rules of conduct, gshin rtsi’i bzhugs so (Tibetan manuscript with tables, 4 pages) - Horoscope of the deceased (Mon). The ritual known as "Opening of the Altan sav" is conducted by a person possessing a profound understanding of the topic, akin to an astrologer who appears to be obtaining insights from an invisible entity and relaying them to the person before him. It is evident from the original materials referenced in the article, their title, and particularly from the context surrounding the identification of the deceased's direction, that the purpose of “Opening of the Altan sav” is to assist both the living and the deceased. The concluding remarks of the texts referenced in this article by Sumbe Khamba Ishbaljir and Luvsandagdan clearly indicate that they adhered to the traditions and cultural practices of the indigenous people who were dominant in their region, which governed their funeral rites. As a result, there are various written versions of the guide for “Opening of the Altan sav,” created to assist the deceased and their families. Алтан сав нээхүй: - Өөд болоочийг нутаглуулах зүгийн тухай Хураангуй: Энэхүү өгүүлэлд өөд болоочийг нутаглуулахад баримтлах зүгийг хэрхэн тогтоодог болохыг тухайлан авч үзэв. Ингэхдээ бидэнд хадгалагдаж буй төвөд эрдэмтэн Санжаажамц (1653-1705)-ын зохиол phug lugs rtsis kyi legs bshad mkhas pa’i mgul rgyan beet’ur dkar po’i do shal dpyod ldan snying nor zhes bya ba bzhugs so (төвөд модон бар, цаасны хэмжээ: 10.3х48.2 см, хуудасны тоо: - 636, мон. Пүг ёсны зурхайн сайн номлол мэргэдийн хоолойн чимэг Биндэргаравын унжлага шинжлэл төгсийн зүрхний эрдэнэ) нэрт номын 343-418 дахь талд буй Үхэгсдийн зурхайн 29 дүгээр бүлэг, монгол эрдэмтэн Сүмбэ хамба Ишбалжир (1704-1788)-ын зохиол gnyis pa gson gshin gang la ni, phan byed gshin rtsis gser snod bcas, dur lnga ngos ‘dzin la sogs pa, phyogs gcig tu ni re’u mig ‘god (төвөд гар бичмэл, цаасны хэмжээ: 8.7х26 см, хуудасны тоо: - 17, мон. Хоёрдугаар амьд, үхсэн алинд нь туслан үйлдэх үхэгсдийн зурхай Алтан сав сэлт, таван үхээрийг танин барих тэргүүтнийг нэг зүгт хүснэгтэд зохиовой), монгол эрдэмтэн Лувсандагданы зохиол gshin rtsis mdor bsdus ‘khyir bde kun phan zhes bya ba bzhigs so (төвөд гар бичмэл, цаасны хэмжээ: 9.8х42 см, хуудасны тоо: - 26, мон. Үхэгсдийн зурхайн товч хураангуй Авахад хялбар бүхнээ туслагч) хэмээх номыг голлон ашиглав. Эдгээрээс гадна, үхэгсдийн зурхайн онолын ном бүтээлээс чухал хэрэгтэйг түүвэрлэн, хэрэглэхэд хялбар болгосон, эмхэтгэгч нь тодорхойгүй beet’ur dkar po’i gshin brtsis mdor bsdus mdo gzhung bzhugs so (төвөд гар бичмэл, 8.6х32 см, хуудасны тоо: - 16, мон. Биндэргаравын үхэгсдийн зурхайн товч хураангуй Судрын гол оршвой), Алтан сав хэмээх судар оршвой (монгол гар бичмэл, цаасны хэмжээ 8.5х30.6, хуудасны тоо: - 21), gson pa bgegs bral dang gshin brtsis bzhugs so (төвөд гар бичмэл, цаасны хэмжээ 18х7.5 см, хуудасны тоо: - 24, мон. Амьдыг тотгороос хагацаах болон Үхэгсдийн зурхай оршвой), gshin rtsi’i rnam bzhag mdor bsdus bya tshul gsal byed me long zhes by aba bzhugs so (төвөд гар бичмэл, хуудасны тоо: - 9, мон. Үхэгсдийн зурхайн тийн агуулгын товч хураангуй Ажил үйлдвэрийг тодруулан үйлдэгч толь хэмээх оршвой), gshin rtsi’i bzhugs so (хүснэгттэй, төвөд гар бичмэл, хуудасны тоо: - 4, мон. Үхэгсдийн зурхай) зэрэг судалгааны хэрэглэгдэхүүн бидэнд хадгалагдаж байна. “Алтан сав нээх” эл зан үйлийг илт мэдэл эрхшээсэн нэгэн үйлдэх учиртайг зурхайч нь араасаа хэн нэгнийг чагнаж, түүний хэлснийг өмнөх хүндээ дамжуулж байгаа шиг төрх байдлыг үзүүлдэг ёс баталж байна. Алтан савыг амьд, үхсэн хоёрт хоёуланд нь туслахын тулд нээдэг болох нь өгүүлэлд ашигласан эх хэрэглэгдэхүүн, тэдний гарчиг, нэн ялангуяа өөд болоочийг нутаглуулах зүгийг тогтоох агуулгаас тодорхой байна. Сүмбэ хамба Ишбалжир, Лувсандагдан нарын энэхүү өгүүлэлд ашигласан зохиолын төгсгөлийн үгээс өөр, өөрийн нутагт өмнө дэлгэрсэн, уугуул ард түмний язгуур болон уламжлалт соёлыг даган баримталж, оршуулах ёслолыг журамладаг байсан нь тодорхой байна. Тийм ч учраас өөд болоочид болон түүний ар гэрийнхэнд туслах зорилготой алтан сав нээх гарын авлагын бичмэл хувилбар олон янз байдаг байна. Түлхүүр үг: Үхэгсдийн зурхай, Сүмбэ хамба Ишбалжир, Лувсандагдан, Хар нохойн ам, Жийлэн, Төрсөн жил, Суусан суудал, Эрхшээсэн мэнгэ, Буусан мэнгэ, Хар мэнгэ, Шарил хөдөлгөх зүг, Нутаглуулах зүг